Root-crown ratio: a new method for measurement of orthodontic external apical root resorption. Issue 1 (27th February 2020) - Gupta, Deepak Kumar; Aggarwal, Kanish
ABSTRACT: Purpose : External Apical Root Resorption (EARR) is an undesirable but unavoidable side effect of orthodontic treatment. The various methods proposed for its evaluation, e.g. Intraoral Periapical (IOPA) X-ray and Orthopantomogram (OPG) x-rays use linear measurements which have errors due to magnification and angulations of x-rays. Root-crown ratio as measured on digital OPGs, which are essential diagnostic records for all orthodontic patients were used for the first time to assess root resorption. Methods : A two-step method was used, first to check the v alidation of OPG measurement with IOPA x rays. The first step involved the measurement of Root-crown ratio on digital OPG and IOPA by 5 independent examiners on IC measure software. The second step involved the measurement of root resorption as Root-crown ratio on pretreatment and post-treatment OPG X rays of 32 treated orthodontic patients all of which were treated by a single orthodontist. Digital OPG images of all patients were traced in Picassa software. In both steps, root-crown ratio was assessed by modified Lind method. Results : The results of first step did not show any significant differences in examiners to read the IOPA and OPG x rays. The results of the second step showed 11.8% root resorption in maxillary central incisors and 4% root resorption in lateral incisors. Similarly, maxillary and mandibular molars showed 1.6% and 5.1% resorption, respectively. The resorption in mandibular molars was significantly more compared to pretreatment value. There was apparently no effect of extraction treatment or treatment time on the amount of resorption. Conclusion : The study concluded that root-crown ratio can be used as an effective and efficient alternative method to quantify root resorption on OPG X rays and possibly alleviate the need for taking IOPA x rays in orthodontic patients thereby reducing the radiation exposure.